A rare case of intracardiac metastasis of uterine leiomyosarcoma - Khadije Mohammadi; Shirin Jafari; Fatemeh Jafari (ARYA Atherosclerosis, 2022)
A 56-year-old woman with past medical history of uterine liomyosarcoma for 4 years ago, referred us for echocardiography to evaluate cardiac function. She was on chemotherapy regimen, but dropped out her treatment 11 months ago due to fear of COVID infection.According to her past medical documents, she also had a history of lung metastasis about 3 years ago that resolved completely with chemotherapy (ifosfamide) and after that, she had been undergone regular interval of chemotherapy until she dropped it. She had no clinical evidence of systemic emboli and just complained of exertional dyspnea.